Role of Ttca of Citrobacter Werkmanii in Bacterial Growth, Biocides Resistance, Biofilm Formation and Swimming Motility - Gang Zhou (International Journal of Molecular Sciences, 2018)
To screen, identify and study the genes involved in isothiazolone resistance and biofilm formation in Citrobacter werkmanii strain BF-6. A Tn5 transposon library of approximately 900 mutants of C. werkmanii strain BF-6 was generated and screened to isolate 1,2-benzisothiazolin-3-one (BIT) resistant strains. In addition, the tRNA 2-thiocytidine (32) synthetase gene (ttcA) was deleted through homologous recombination and the resulting phenotypic changes of the ΔttcA mutant were studied. A total of 3 genes were successfully identified, among which ΔttcA mutant exhibited a reduction in growth rate and swimming motility. On the other hand, an increase in biofilms formation in ΔttcA were observed but not with a significant resistance enhancement to BIT. This work, for the first time, highlights the role of ttcA gene of C. werkmanii strain BF-6 in BIT resistance and biofilm formation.